A preparation process of thermal sensitive coating and thermal sensitive paper

By preparing a thermal coating containing ultraviolet absorbers and thermal dye microspheres, the problem of poor image stability of thermal paper is solved, and the high-performance characteristics of thermal paper are achieved, including waterproofing, flame retardant and friction-resistant performance improvements.

CN119041239BActive Publication Date: 2025-04-25JIANGSU JINDA PACKAGING MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411063389.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-04-25
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The poor image stability of existing thermal papers limits its application range and the demand for high-performance thermal papers is gradually increasing.

Method used

A thermally sensitive coating preparation process is adopted to prepare an ultraviolet absorber by reacting 2,4-dihydroxybenzophenone with glycidyl methacrylate, and a thermally sensitive dye microsphere is prepared by reacting colorless dye, modified color developer, sensitizer with urea, formaldehyde and vinyl. The thermally sensitive coating is prepared by reacting with a modified emulsion.

Benefits of technology

It improves the waterproofing, flame retardant and friction-proof performance of thermal paper, enhances the stability and friction-resistant image, and meets the needs of high-performance thermal paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005327182050000031
    Figure GDA0005327182050000031
  • Figure GDA0005327182050000032
    Figure GDA0005327182050000032
  • Figure GDA0005327182050000161
    Figure GDA0005327182050000161
Patent Text Reader

Abstract

The invention discloses a preparation process of a thermosensitive coating and thermosensitive paper, and relates to the field of thermosensitive paper. When preparing the thermosensitive coating, the invention reacts 2,4-dihydroxybenzophenone and glycidyl methacrylate to obtain an ultraviolet absorber; reacts a core liquid made of a colorless dye, a modified developer, a sensitizer, and tetradecanol with urea, formaldehyde, and vinyl aldehyde to obtain thermosensitive dye microspheres; reacts methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, and an ultraviolet absorber to obtain a modified emulsion; and reacts thermosensitive dye microspheres, palladium acetate, and a modified emulsion to obtain a thermosensitive coating. The thermosensitive coating prepared by the invention has good waterproof performance, flame retardant performance, and anti-friction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal paper, in particular to a preparation process of a thermal coating and thermal paper. Background Art

[0002] As a type of information recording material, thermal paper has the characteristics of small and flexible printing device, single and cheap printing consumables, simple and convenient printing operation, quiet and fast printing process, and fine and clear printed products. It has been widely used in fax communications, medical imaging, financial bills, logistics labels and other fields.

[0003] Since the thermal recording method has the characteristics of being completely dry, not requiring a developing and fixing process, having no smoke smell during recording, no noise, high resolution, being able to make color copies, and being easy to operate, thermal paper has gradually replaced other traditional methods with the development of electronic computer terminal technology and non-printing printers. However, the poor image stability of thermal paper also has many restrictions on its application, and with the continuous expansion of the application range of thermal paper, the demand for high-performance thermal paper is becoming increasingly strong. The thermal paper prepared by the present invention has good waterproof performance, flame retardant performance and anti-friction performance, and has good market prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process of a heat-sensitive coating to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A preparation process of a thermosensitive coating, wherein the thermosensitive coating is prepared by reacting a core liquid made of a colorless dye, a modified developer, a sensitizer, and tetradecanol with urea, formaldehyde, and vinyl aldehyde to obtain thermosensitive dye microspheres; a modified latex is prepared by reacting methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silicon dioxide, and an ultraviolet absorber; and the thermosensitive dye microspheres, palladium acetate, and the modified latex are reacted to obtain the coating.

[0007] A preparation process of a heat-sensitive coating comprises the following preparation steps:

[0008] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene are mixed in a mass ratio of 1:(1.3-1.7):(10-20), the pH value is adjusted to 10-11 with 1 mol / l sodium hydroxide solution, the mixture is stirred at 400-600 r / min for 6-8 hours at room temperature, cooled to room temperature, filtered, the residue is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 40-50° C. for 3-5 hours to obtain a UV absorber;

[0009] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 are mixed in a mass ratio of 1: (5-6): (50-60): (5-7) to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount of 8 to 12 times the mass of allyl trimethoxysilane is added, and the mixture is stirred at 800 to 1000 r / min at 65 to 75° C. for 7 to 9 hours, and the precipitate is separated by centrifugation, and the precipitate is washed with anhydrous ethanol for 3 to 5 times, and freeze-dried for 7 to 9 hours to obtain modified silica; the modified silica and anhydrous ethanol are mixed in a mass ratio of 1: (8-12), and ultrasonicated in a cell crusher at 500 W for 1 to 2 hours, filtered, and the filter residue is freeze-dried for 7 to 9 hours to obtain flaky modified silica;

[0010] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium lauryl sulfate, and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (0.8-1.2): (1-1.2): (1-1.4): (0.01-0.02): (0.017-0.019): (2-4), and stirred at 45-55° C. and 800-1200 r / min for 20-40 min to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium lauryl sulfate, deionized water, and sodium bicarbonate are mixed in a mass ratio of 1: (0.7-0.9): (0.8-1.2): (1-1.2): (1-1.4): (0.01-0.02): (0.017-0.019): (2-4) to obtain a pre-emulsion; :(0.008~0.012):(0.008~0.012):(0.8~1.2):(0.003~0.007) mix well, add pre-emulsion with the mass of 0.3~0.7 times of the polyvinyl alcohol solution and initiator solution with the mass of 0.3~0.7 times of the polyvinyl alcohol solution, stir at 800~1200r / min for 20~40min at 75~85℃, add pre-emulsion with the mass of 1~2 times of the polyvinyl alcohol solution and initiator solution with the mass of 0.8~1.2 times of the polyvinyl alcohol solution dropwise within 2~4h, continue stirring for 20~40min, adjust pH to 8~10 with aqueous ammonia to obtain modified emulsion;

[0011] (4) Mix m-hydroxyphenylethylamine, triethylamine and chloroform in a mass ratio of 1: (0.8-1): (20-30), and drip ethylphosphoric acid dichloride (1.3-1.7 times the mass of m-hydroxyphenylethylamine) at 0-5° C. at a rate of 40-60 drops / min. After the dripping is completed, stir at 400-600 r / min for 1-3 hours, heat to room temperature and continue stirring for 10-14 hours, filter, take the filtrate, wash the filtrate with deionized water for 3-5 times, and vacuum dry at 40-50° C. for 3-5 hours to obtain a modified color developer;

[0012] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1: (1.2-1.4): (1-1.4): (10-20): (1-1.2), and stir at 200-300 r / min for 20-40 min at 65-75° C. under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1: (8-12): (80-100), and add the mixture to the mixture using a homogenizer at room temperature for 6000 rpm. ~10000r / min stirring for 2~4min, adjusting the pH to 3~3.5 with 1mol / L hydrochloric acid, dropping 3~5 times the mass of urea with a 37% formaldehyde solution and 0.09~0.11 times the mass of urea with ethylene aldehyde, stirring at 50~60℃ and 400~600r / min for 2~4h, cooling to room temperature, filtering, washing the filter residue with deionized water and anhydrous ethanol for 3~5 times respectively, and vacuum drying at 40~50℃ for 3~5h to obtain thermosensitive dye microspheres;

[0013] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex are mixed in a mass ratio of 1: (0.05-0.15): (1.5-2.5), stirred at 800-1200 r / min at 50-60° C. for 6-10 h, and cooled to room temperature to obtain a thermosensitive coating.

[0014] As an optimization, the reaction process for preparing the ultraviolet absorber in step (1) is as follows:

[0015]

[0016] As an optimization, the initiator solution in step (3) is prepared by mixing ammonium persulfate and deionized water in a mass ratio of 1:20.

[0017] As an optimization, the method for preparing the polyvinyl alcohol solution in step (3) is: mix polyvinyl alcohol and deionized water in a mass ratio of 1:10, and stir at 85°C and 600-800 r / min for 1-2 hours.

[0018] As an optimization, the reaction process for preparing the modified developer in step (4) is as follows:

[0019]

[0020] As an optimization, the colorless dye in step (5) is a fluoran dye.

[0021] As an optimization, the sensitizer in step (5) is 1,2-diphenoxyethane.

[0022] As an optimization, the thermal coating is applied to the thermal paper.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] When preparing the heat-sensitive coating, the present invention comprises the following steps: reacting 2,4-dihydroxybenzophenone with glycidyl methacrylate to obtain an ultraviolet absorber; reacting a core liquid made of a colorless dye, a modified developer, a sensitizer, and tetradecanol with urea, formaldehyde, and vinyl aldehyde to obtain heat-sensitive dye microspheres; and reacting methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silicon dioxide, and an ultraviolet absorber to obtain a heat-sensitive coating.

[0025] Firstly, m-hydroxyphenylethylamine is reacted with dichloroethylphosphoric acid to obtain a modified color developer containing phenolic hydroxyl groups at both ends. The phenolic hydroxyl structure releases protons in a certain medium and at a certain temperature, inducing the ring-opening of the fluorane colorless dye lactone ring to develop color, and the introduced phosphorus element can provide a certain flame retardant effect, thereby improving the flame retardant properties of the thermal sensitive coating; the core liquid made of colorless dye, modified color developer, sensitizer and tetradecanol is reacted with urea, formaldehyde and vinyl aldehyde to obtain thermal sensitive dye microspheres. The microsphere material obtained by the reaction of urea with formaldehyde and vinyl aldehyde is urea-formaldehyde resin with double bonds. The urea-formaldehyde resin as a shell layer can not only separate the colorless dye, modified color developer, sensitizer and tetradecanol from other components of the coating, thereby improving the friction resistance of the thermal sensitive coating, but also provide double bonds as reaction sites, reacting with silicon hydrogen in the modified emulsion to form stable crosslinks, thereby further improving the friction resistance.

[0026] Secondly, the ultraviolet absorber prepared by the reaction of 2,4-dihydroxybenzophenone and glycidyl methacrylate has a double bond, which can react with silicon hydrogen in the modified emulsion to form a stable crosslink, so that the thermal paper has stable ultraviolet absorption performance; methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, and ultraviolet absorber are prepared by double bond polymerization to obtain a modified emulsion, which is mixed with a thermal dye and then coated on the surface of the paper to form a protective film layer, thereby improving the waterproof performance of the thermal paper; the flaky modified silica is a nano-flaky structure, which is dispersed in the thermal coating after cross-linking reaction with the emulsion, extending the diffusion path, and can effectively prevent water from diffusing into the paper, thereby improving the waterproof ability of the thermal paper, and the flaky modified silica is dispersed in the thermal coating as an inorganic filler, which also improves the anti-friction performance of the thermal coating on the thermal paper. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A preparation process of a heat-sensitive coating comprises the following steps:

[0030] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.3:10, the pH was adjusted to 10 with a 1 mol / l sodium hydroxide solution, stirred at 400 r / min for 6 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 3 times, and vacuum dried at 40° C. for 3 h to obtain a UV absorber;

[0031] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5:50:5 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount of 8 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 800 r / min at 65° C. for 7 h, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 3 times, and freeze-dried for 7 h to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:8, and ultrasonicated in a cell crusher at 500 W for 1 h, filtered, and the filter residue was freeze-dried for 7 h to obtain flaky modified silica;

[0032] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.7:0.8:1:1:0.01:0.017:2, and stirred at 800 r / min for 20 min at 45°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, and sodium bicarbonate are mixed. Mix at a mass ratio of 1:0.008:0.008:0.8:0.003, add a pre-emulsion of 0.3 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.3 times the mass of the polyvinyl alcohol solution, stir at 800 r / min for 20 min at 75°C, dropwise add a pre-emulsion of 1 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.8 times the mass of the polyvinyl alcohol solution within 2 h, continue stirring for 20 min, adjust the pH to 8 with aqueous ammonia to obtain a modified emulsion;

[0033] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.8:20, and dichloroethylphosphoric acid (1.3 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 40 drops / min at 0°C. After the addition was completed, the mixture was stirred at 400 r / min for 1 hour, the mixture was heated to room temperature and continued to be stirred for 10 hours. The mixture was filtered, the filtrate was taken, and the filtrate was washed three times with deionized water, and vacuum dried at 40°C for 3 hours to obtain a modified color developer.

[0034] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.2:1:10:1, and stir at 200 r / min for 20 min at 65°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:8:80 and add them, stir at 6000 r / min for 2 min at room temperature with a homogenizer, adjust the pH to 3 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 3 times the mass of urea and 0.09 times the mass of ethylene aldehyde, stir at 400 r / min for 2 h at 50°C, cool to room temperature, filter, wash the residue with deionized water and anhydrous ethanol for 3 times, and vacuum dry at 40°C for 3 h to obtain thermosensitive dye microspheres;

[0035] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.05:1.5, stirred at 800 r / min at 50° C. for 6 h, and cooled to room temperature to obtain a thermosensitive coating.

[0036] Example 2

[0037] A preparation process of a heat-sensitive coating comprises the following steps:

[0038] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0039] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0040] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0041] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0042] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0043] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0044] Example 3

[0045] A preparation process of a heat-sensitive coating comprises the following steps:

[0046] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.7:20, the pH value was adjusted to 11 with a 1 mol / l sodium hydroxide solution, stirred at 600 r / min for 8 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 5 times, and vacuum dried at 50° C. for 5 h to obtain a UV absorber;

[0047] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:6:60:7 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 12 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 1000 r / min at 75°C for 9 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 5 times, and freeze-dried for 9 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:12, and ultrasonicated at 500 W for 2 hours in a cell crusher, and filtered, and the filter residue was freeze-dried for 9 hours to obtain flaky modified silica;

[0048] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.9:1.2:1.2:1.4:0.02:0.019:4, and stirred at 1200 r / min for 40 min at 55°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, and bicarbonate of soda are mixed. Sodium was mixed at a mass ratio of 1:0.012:0.012:1.2:0.007, a pre-emulsion of 0.7 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.7 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1200 r / min for 40 min at 85°C, a pre-emulsion of 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1.2 times the mass of the polyvinyl alcohol solution were added dropwise within 4 h, and the stirring was continued for 40 min. The pH was adjusted to 10 with aqueous ammonia to obtain a modified emulsion;

[0049] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:1:30, and dichloroethylphosphoric acid (1.7 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 60 drops / min at 5°C. After the addition was completed, the mixture was stirred at 600 r / min for 3 h, the mixture was heated to room temperature and continued to be stirred for 14 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 5 times, and vacuum dried at 50°C for 5 h to obtain a modified color developer;

[0050] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.4:1.4:20:1.2, and stir at 300 r / min for 40 min at 75°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:12:100 and add them, stir at 10000 r / min for 4 min at room temperature with a homogenizer, adjust the pH to 3.5 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 5 times the mass of urea and 0.11 times the mass of ethylene aldehyde, stir at 60°C for 4 h, cool to room temperature, filter, wash the residue with deionized water and anhydrous ethanol for 5 times, and vacuum dry at 50°C for 5 h to obtain thermosensitive dye microspheres;

[0051] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.15:2.5, stirred at 1200 r / min for 10 h at 60° C., and cooled to room temperature to obtain a thermosensitive coating.

[0052] Comparative Example 1

[0053] A preparation process of a heat-sensitive coating comprises the following steps:

[0054] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0055] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0056] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0057] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0058] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0059] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0060] Comparative Example 2

[0061] A preparation process of a heat-sensitive coating comprises the following steps:

[0062] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0063] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0064] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0065] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0066] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0067] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0068] Comparative Example 3

[0069] A preparation process of a heat-sensitive coating comprises the following steps:

[0070] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0071] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0072] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0073] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0074] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0075] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0076] Comparative Example 4

[0077] A preparation process of a heat-sensitive coating comprises the following steps:

[0078] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0079] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0080] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0081] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0082] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0083] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0084] Comparative Example 5

[0085] A preparation process of a heat-sensitive coating comprises the following steps:

[0086] (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate, and toluene were mixed in a mass ratio of 1:1.5:15, the pH value was adjusted to 10.5 with 1 mol / l sodium hydroxide solution, stirred at 500 r / min for 7 h at room temperature, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 45° C. for 4 h to obtain a UV absorber;

[0087] (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 were mixed in a mass ratio of 1:5.5:55:6 to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount 10 times the mass of allyl trimethoxysilane was added, and the mixture was stirred at 900 r / min at 70°C for 8 hours, and the precipitate was separated by centrifugation. The precipitate was washed with anhydrous ethanol for 4 times, and freeze-dried for 8 hours to obtain modified silica; the modified silica and anhydrous ethanol were mixed in a mass ratio of 1:10, and ultrasonicated at 500 W for 1.5 hours in a cell crusher, filtered, and the filter residue was freeze-dried for 8 hours to obtain flaky modified silica;

[0088] (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, ultraviolet absorber, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:1:1.1:1.2:0.015:0.018:3, and stirred at 1000 r / min for 30 min at 50°C to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate, deionized water, carbon Sodium bicarbonate was mixed at a mass ratio of 1:0.01:0.01:1:0.005, a pre-emulsion of 0.5 times the mass of the polyvinyl alcohol solution and an initiator solution of 0.5 times the mass of the polyvinyl alcohol solution were added, and the mixture was stirred at 1000 r / min for 30 min at 80°C, and a pre-emulsion of 1 to 2 times the mass of the polyvinyl alcohol solution and an initiator solution of 1 times the mass of the polyvinyl alcohol solution were added dropwise within 3 h, and the stirring was continued for 30 min. The pH was adjusted to 9 with aqueous ammonia to obtain a modified emulsion;

[0089] (4) m-Hydroxyphenylethylamine, triethylamine and chloroform were mixed in a mass ratio of 1:0.9:25, and dichloroethylphosphoric acid (1.5 times the mass of m-Hydroxyphenylethylamine) was added dropwise at 50 drops / min at 2.5°C. After the addition was completed, the mixture was stirred at 500 r / min for 2 h, heated to room temperature and continued to stir for 12 h, filtered, and the filtrate was taken. The filtrate was washed with deionized water for 4 times, and vacuum dried at 45°C for 4 h to obtain a modified color developer;

[0090] (5) Mix the colorless dye, modified developer, sensitizer, and tetradecanol in a mass ratio of 1:1.3:1.2:15:1.1, and stir at 250 r / min for 30 min at 70°C under nitrogen protection to obtain a core liquid; mix resorcinol, urea, and a 10% polyvinyl alcohol aqueous solution in a mass ratio of 1:10:90 and add them, stir at 8000 r / min for 3 min at room temperature with a homogenizer, adjust the pH to 3.25 with 1 mol / L hydrochloric acid, add a 37% formaldehyde solution with a mass concentration of 4 times the mass of urea and 0.1 times the mass of ethylene aldehyde, stir at 500 r / min for 3 h at 55°C, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 4 times, and vacuum dry at 45°C for 4 h to obtain thermosensitive dye microspheres;

[0091] (6) The thermosensitive dye microspheres, palladium acetate, and modified latex were mixed in a mass ratio of 1:0.1:2, stirred at 1000 r / min for 8 h at 55° C., and cooled to room temperature to obtain a thermosensitive coating.

[0092] Test Example 1

[0093] Anti-friction performance:

[0094] Test method: By referring to GB / T28210-2011 "Thermal Paper", the anti-friction performance of the thermal paper prepared by the thermal coating of each embodiment and comparative example was tested, and the results were expressed as image retention rate. The results are shown in Table 1.

[0095] Table 1

[0096] Image retention rate (%) Image retention rate (%) Example 1 92.5 Comparative Example 1 84.7 Example 2 93.1 Comparative Example 2 92.8 Example 3 93.2 Comparative Example 3 88.3 Comparative Example 4 93.1 Comparative Example 5 81.7

[0097] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the heat-sensitive coating prepared in the present invention has good anti-friction performance.

[0098] By comparison, the image retention rates of Examples 1 to 3 are significantly greater than that of Comparative Example 1, indicating that microspheres are prepared by the reaction of urea with formaldehyde and ethylene aldehyde, and the microspheres use urea-formaldehyde resin as a shell layer, which can effectively improve the friction resistance of the thermal coating, and the shell layer can also provide double bonds as reaction sites, which react with silicon hydrogen in the modified emulsion to form stable crosslinks, further improving the friction resistance; the image retention rates of Examples 1 to 3 are significantly greater than that of Comparative Example 3, indicating that methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, and ultraviolet absorber are used to prepare the modified emulsion through the polymerization reaction of double bonds, and the introduction of silane improves the friction resistance of the thermal coating; the image retention rates of Examples 1 to 3 are significantly greater than that of Comparative Example 5, indicating that flaky modified silica is dispersed in the thermal coating as an inorganic filler, effectively improving its friction resistance.

[0099] Test Example 2

[0100] Flame retardant performance test:

[0101] Test method: The thermal papers prepared by the thermal coatings of the embodiments and comparative examples were cut into standard strips with a length of 100 mm and a width of 10 mm, and the limiting oxygen index of the standard strips was tested. The results are shown in Table 2.

[0102] Table 2

[0103] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.1 Comparative Example 1 32.2 Example 2 32.5 Comparative Example 2 31.8 Example 3 31.9 Comparative Example 3 31.4 Comparative Example 4 20.6 Comparative Example 5 24.1

[0104] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the heat-sensitive coating prepared by the present invention has good flame retardant properties.

[0105] By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 4, indicating that the modified developer containing phenolic hydroxyl groups at both ends is prepared by reacting m-hydroxyphenylethylamine with dichloroethyl phosphoric acid, and the introduced phosphorus element can provide a certain flame retardant effect, thereby improving the flame retardant properties of thermal paper; the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 5, indicating that flaky modified silicon dioxide as an inorganic filler dispersed in the thermal coating can effectively block the diffusion of combustible gases, thereby improving the flame retardant properties of the thermal coating.

[0106] Test Example 3

[0107] Waterproof performance test:

[0108] Test method: By referring to GB / T28210-2011 "Thermal Paper", the waterproof performance of the thermal paper prepared by the thermal coating of each embodiment and comparative example was tested, and the results were expressed as image retention rate. The results are shown in Table 3.

[0109] Table 3

[0110]

[0111]

[0112] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the heat-sensitive coating prepared by the present invention has good waterproof performance.

[0113] By comparison, the image retention rates of Examples 1 to 3 are significantly greater than that of Comparative Example 1, indicating that the core liquid made of fluorane dyes, modified developers, sensitizers, and tetradecanol reacts with urea, formaldehyde, and vinyl aldehyde to prepare thermosensitive dye microspheres, and the thermosensitive dye microspheres use urea-formaldehyde resin as a shell layer to effectively improve the waterproof performance of the thermosensitive coating; the image retention rates of Examples 1 to 3 are significantly greater than that of Comparative Example 5, indicating that the flaky modified silica is a nano-flaky structure, which is dispersed in the thermosensitive coating after cross-linking reaction with the emulsion, extending the diffusion path, and can effectively prevent water from diffusing into the paper, thereby improving the waterproof ability of the thermosensitive coating.

[0114] Test Example 4

[0115] Anti-ultraviolet aging performance:

[0116] Test method: Cut the thermal papers prepared by the thermal coatings of the embodiments and comparative examples into 100mm×100mm pieces, place them on the carrier of the ZF-2 three-purpose UV instrument, adjust the height so that the film is 10cm away from the light source, irradiate with 365nm light for 3 days, and observe the yellowing of the thermal paper. The results are shown in Table 4.

[0117] Table 4

[0118]

[0119]

[0120] From the comparison of the results of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the heat-sensitive coating prepared in the present invention has good anti-ultraviolet aging performance.

[0121] By comparison, the thermal papers of Examples 1 to 3 did not turn yellow, while the thermal paper of Comparative Example 2 turned yellow, indicating that the ultraviolet absorber participated in the polymerization during the preparation of the modified emulsion and was able to absorb ultraviolet rays, so that the thermal coating had anti-ultraviolet aging performance.

[0122] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A process for preparing a heat-sensitive coating, characterized in that: The method comprises the following preparation steps: (1) 2,4-dihydroxybenzophenone, glycidyl methacrylate and toluene are mixed in a mass ratio of 1: (1.3-1.7): (10-20), the pH value is adjusted to 10-11 with 1 mol / l sodium hydroxide solution, stirred at 400-600 r / min for 6-8 h at room temperature, cooled to room temperature, filtered, and the residue is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 40-50°C for 3-5 h to obtain a UV absorber; (2) Allyl trimethoxysilane, tetraethyl orthosilicate, toluene, and Span 80 are mixed in a mass ratio of 1: (5-6): (50-60): (5-7) to form an oil phase, and a hydrochloric acid aqueous solution with a pH of 2.5 in an amount of 8 to 12 times the mass of allyl trimethoxysilane is added, and the mixture is stirred at 800 to 1000 r / min at 65 to 75°C for 7 to 9 hours, and the precipitate is separated by centrifugation. The precipitate is washed with anhydrous ethanol for 3 to 5 times, and freeze-dried for 7 to 9 hours to obtain modified silica; the modified silica and anhydrous ethanol are mixed in a mass ratio of 1: (8-12), and ultrasonicated in a cell crusher at 500 W for 1 to 2 hours, filtered, and the filter residue is freeze-dried for 7 to 9 hours to obtain flaky modified silica; (3) Methyl methacrylate, butyl acrylate, allyl dimethyl silane, flaky modified silica, UV absorber, alkylphenol polyoxyethylene ether, sodium lauryl sulfate, and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (0.8-1.2): (1-1.2): (1-1.4): (0.01-0.02): (0.017-0.019): (2-4), and stirred at 45-55°C at 800-1200 r / min for 20-40 min to prepare a pre-emulsion; polyvinyl alcohol solution, alkylphenol polyoxyethylene ether, sodium lauryl sulfate, deionized water, and sodium bicarbonate are mixed in a mass ratio of 1: (0.7-0.9): (0.8-1.2): (1-1.2): (1-1.4): (0.01-0.02): (0.017-0.019): (2-4) to obtain a pre-emulsion; :(0.008~0.012):(0.008~0.012):(0.8~1.2):(0.003~0.007)Mix evenly, add pre-emulsion with the mass of 0.3~0.7 times of the mass of the polyvinyl alcohol solution and initiator solution with the mass of 0.3~0.7 times of the mass of the polyvinyl alcohol solution, stir at 800~1200r / min for 20~40min at 75~85℃, drop pre-emulsion with the mass of 1~2 times of the mass of the polyvinyl alcohol solution and initiator solution with the mass of 0.8~1.2 times of the mass of the polyvinyl alcohol solution within 2~4h, continue stirring for 20~40min, adjust pH to 8~10 with aqueous ammonia to obtain modified emulsion; (4) Mix m-hydroxyphenylethylamine, triethylamine and chloroform in a mass ratio of 1: (0.8-1): (20-30), add dichloroethylphosphoric acid (1.3-1.7 times the mass of m-hydroxyphenylethylamine) at 0-5°C at a rate of 40-60 drops / min, stir at 400-600 r / min for 1-3 hours after the addition is complete, heat to room temperature and continue stirring for 10-14 hours, filter, take the filtrate, wash the filtrate with deionized water for 3-5 times, and vacuum dry at 40-50°C for 3-5 hours to obtain a modified color developer; (5) Mix the colorless dye, modified color developer, sensitizer and tetradecanol, and stir at 200-300 r / min for 20-40 min at 65-75°C under nitrogen protection to prepare the core liquid; mix resorcinol, urea and 10% polyvinyl alcohol aqueous solution in a mass ratio of 1: (8-12): (80-100) and add them, and stir at 6000-10000 r / min with a homogenizer at room temperature for 2-4 min. , adjust the pH to 3-3.5 with 1 mol / L hydrochloric acid, add dropwise 3-5 times the mass of urea formaldehyde solution with a mass concentration of 37% and 0.09-0.11 times the mass of urea ethylene aldehyde, stir at 400-600 r / min for 2-4 hours at 50-60°C, cool to room temperature, filter, wash the residue with deionized water and anhydrous ethanol for 3-5 times, respectively, and vacuum dry at 40-50°C for 3-5 hours to obtain thermosensitive dye microspheres; The colorless dye is a fluorane dye; (6) Mix the thermosensitive dye microspheres, palladium acetate and modified latex in a mass ratio of 1: (0.05-0.15): (1.5-2.5), stir at 800-1200 r / min at 50-60°C for 6-10 h, and cool to room temperature to obtain a thermosensitive coating.

2. The preparation process of a heat-sensitive coating according to claim 1, characterized in that: The initiator solution in step (3) is prepared by mixing ammonium persulfate and deionized water in a mass ratio of 1:

20.

3. The preparation process of a heat-sensitive coating according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol solution in step (3) is as follows: polyvinyl alcohol and deionized water are mixed in a mass ratio of 1:10, and stirred at 85°C and 600-800 r / min for 1-2 hours.

4. The preparation process of a heat-sensitive coating according to claim 1, characterized in that: The sensitizer in step (5) is 1,2-diphenoxyethane.

5. A thermal paper, characterized in that: The thermal coating used in the thermal paper is the thermal coating according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Reversible thermosensitive color-changing microcapsule material as well as preparation method and application thereof

    CN116393054A

  • Microcapsule type temperature-sensitive color-changing art coating and preparation method thereof

    CN117965058A